Financial Literacy Survey - Alpha Research (World Bank, Washington, DC, 2013)
The Financial Literacy survey is part of a World Bank Financial Governance Consumer Protection in Financial Services Program, which aims to improve the levels of consumer protection and financial literacy and thereby strengthen consumer confidence in the financial sectors. The objective of the study is to assess the level of financial literacy and consumer confidence of households and to outline the peculiarities in different target groups prior to the implementation of the action plan for increasing the financial literacy of the general population and, in particular, of low-income groups. The questionnaire is based on the model Financial literacy survey questionnaire used in Romania in order to achieve comparison of the results between the countries. The graphs and tables included in the report are based on the data, collected by the Financial Literacy survey in Bulgaria. The report is structured in two main parts and 3 Annexes: Part One covers methodological approach and research activities, and socio-demographic structure of the sample. Part Two presents the survey results in six chapters: level of confidence in the financial sector; awareness and consumer rights in the use of financial products; financial literacy; household financial management; interest and use of financial products; key findings and recommendations. There are three annexes: Survey questionnaire; frequencies of the survey questions; and cross-tabulations of all the questions by socio-demographic profile of the respondents.